THE BRIDGE OF HEARTS FROM AMASYA TO NAVOIY: "FERHAT AND ŞIRIN LOVERS MUSEUM" - Orbay, Keziban; Orbay, Metin (ILIM hám JÁMIYET, 2021)
The masterpiece widely known in the Anatolian geography, "Ferhad ü Şirin" was penned as an immortal love story by Ali Şir Nevâyî, the man of wisdom in Turkish Cultural History. The story naturally underwent some changes in its transition from written texts to oral literature and hence many variations have emerged. In this transition, the historical and geographical framework of the story also changed, and it was adapted to Anatolia. The Amasya variant is one of these different forms. This study aimed to provide essential information about the place where the story took place in the Amasya variation. The dominant culture brought to the forefront by the rapid urbanization and emerging globalization in the last century has threatened our intangible cultural heritage, especially our love stories. The "Ferhat and Şirin Lovers Museum" was founded in Amasya in line with the fact that museums are one of the effective methods of transferring intangible cultural heritage from generation to generation. The study set out to introduce this museum in general, discuss its place in tourism since its foundation and the shortcomings observed in its operation and provide ideas for more effective and active use of the museum.